Sulfide solid electrolyte material and battery using same
By introducing oxide layers and optimizing layer structure and element composition into sulfide solid electrolyte materials, the problem of hydrogen sulfur gas generation during contact with humidity is solved, and the safety and stability of the battery is improved, while maintaining high ionic conductivity.
Patent Information
- Application Number
- JP2024036691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-09-08
- Filing Date
- 2024-03-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2038-07-09
AI Technical Summary
Sulfide solid electrolyte materials are prone to generate harmful hydrogen-sulfur gas when exposed to humidity, affecting the safety and stability of the battery.
A sulfide solid electrolyte material is used in a core-shell structure composed of a sulfide layer and an oxide layer. The sulfide layer contains lithium, phosphorus, sulfur and halogen elements, and the oxide layer is located on the surface of the sulfide layer. By adjusting the layer structure and element composition, the peak intensity ratio in the P-NMR spectrum is controlled to reduce the formation of hydrogen sulfur gas.
It effectively reduces the amount of hydrogen sulfur gas generated by sulfide solid electrolyte materials when contacting humidity, improves the safety and stability of the battery, and maintains high ionic conductivity.
Smart Images

Figure 0007660290000002 
Figure 0007660290000003 
Figure 0007660290000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sulfide solid electrolyte material and a battery using the same. [Background technology]
[0002] A lithium secondary battery comprises a positive electrode, a negative electrode, and an electrolyte layer disposed between them. The electrolyte layer contains a non-aqueous electrolyte or a solid electrolyte. Since widely used electrolytes are flammable, lithium secondary batteries using electrolytes require a system to ensure safety. Since solid electrolytes are non-flammable, the above system can be simplified. Batteries using solid electrolytes are called all-solid-state batteries.
[0003] Solid electrolytes are broadly divided into organic solid electrolytes and inorganic solid electrolytes. The former are also called polymer solid electrolytes. The ionic conductivity of organic solid electrolytes at room temperature is 10 -6 Since the conductivity of organic solid electrolytes is about 1.2 S / cm, it is difficult to operate all-solid-state batteries using organic solid electrolytes at room temperature. The latter include oxide solid electrolytes and sulfide solid electrolytes.
[0004] Patent Document 1 discloses a sulfide solid electrolyte compound for lithium ion batteries having a cubic Argyrodite-type crystal structure. Patent Document 2 discloses sulfide solid electrolyte particles having an oxide layer formed by oxidizing the particles themselves on the surface. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 104702 [Patent Document 2] JP 2012-94445 A Summary of the Invention [Problem to be solved by the invention]
[0006] A sulfide solid electrolyte has a problem in that it is prone to generating harmful hydrogen sulfide. The present disclosure provides a sulfide solid electrolyte material that generates a small amount of hydrogen sulfide. [Means for solving the problem]
[0007] A sulfide solid electrolyte material according to one embodiment of the present disclosure includes a sulfide layer including a sulfide containing lithium, phosphorus, a halogen, and sulfur, and an oxide layer disposed on the sulfide layer and including an oxide containing lithium, phosphorus, the halogen, and oxygen. 31 In the P-NMR spectrum, the intensity of a first peak component defined in a chemical shift range of 87.6 ppm to 88.4 ppm is 0.42 times or less than the intensity of a second peak component defined in a chemical shift range of 83.6 ppm to 84.4 ppm. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a sulfide solid electrolyte material that generates a small amount of hydrogen sulfide. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of a sulfide solid electrolyte material according to the first embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of the battery according to the second embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view of an electrolyte layer according to a modified example. [Figure 4] FIG. 4 is a graph showing the results of 31P-NMR measurement of the sulfide solid electrolyte materials of Example 1, Comparative Example 1, and Comparative Example 4. [Diagram 5] FIG. 5 is a graph showing the results of XPS measurement of the sulfide solid electrolyte material of Example 1. [Figure 6] FIG. 6 is a graph showing the results of 31P-NMR measurement of the sulfide solid electrolyte materials of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Findings on which this disclosure is based) A problem with common sulfide solid electrolyte materials is that harmful hydrogen sulfide gas is generated when they come into contact with moisture. Patent Document 1 discloses that a sulfide solid electrolyte material that generates a small amount of hydrogen sulfide can be provided by appropriately adjusting the constituent elements and composition of a sulfide solid electrolyte material having a cubic Argyrodite crystal structure. Patent Document 2 discloses that the sulfide solid electrolyte particles disclosed can suppress the generation of a high resistance layer caused by the reaction between an oxide active material and a sulfide solid electrolyte material. However, the relationship between the presence or absence of an oxide layer in a sulfide solid electrolyte material and the amount of hydrogen sulfide generated has not been clarified.
[0011] In general, sulfide materials have high ionic conductivity and generate a large amount of hydrogen sulfide from them. Oxide materials have low ionic conductivity and generate a small amount of hydrogen sulfide from them. If an oxide layer made of an oxide material is disposed only on the surface layer of a sulfide solid electrolyte material that comes into direct contact with moisture, the oxide layer prevents the sulfide layer from coming into direct contact with moisture. Therefore, the amount of hydrogen sulfide generated can be reduced while maintaining high ionic conductivity.
[0012] The sulfide solid electrolyte material according to the first aspect of the present disclosure is a sulfide layer comprising a sulfide material; an oxide layer comprising an oxide of the sulfide material; Equipped with the oxide layer is located on a surface of the sulfide layer; The sulfide material contains Li, P, S and a halogen element X as constituent elements, 31 In a spectrum obtained by P-NMR measurement, when a peak component near 88 ppm is defined as a first peak component, the peak intensity of the first peak component is defined as Za, a peak component near 84 ppm is defined as a second peak component, and the peak intensity of the second peak component is defined as Zb, Za / Zb≦0.42 is satisfied.
[0013] According to the first aspect, it is possible to provide a sulfide solid electrolyte material that generates a small amount of hydrogen sulfide.
[0014] In a second aspect of the present disclosure, for example, the halogen element X of the sulfide solid electrolyte material according to the first aspect is I. According to the second aspect, the ion conductivity can be further improved and the amount of hydrogen sulfide generated can be more sufficiently suppressed.
[0015] In a third aspect of the present disclosure, for example, the sulfide material of the sulfide solid electrolyte material according to the first or second aspect is Li 2 SP 2 S 5 - Includes LiX. 2 SP 2 S 5 When -LiX is included in the sulfide layer as a sulfide material, the discharge characteristics of the battery are further improved.
[0016] In a fourth aspect of the present disclosure, for example, the sulfide material of the sulfide solid electrolyte material according to any one of the first to third aspects is Li 2 SP 2 S 5 According to a fourth aspect, The ionic conductivity is further improved and the amount of hydrogen sulfide generated can be more sufficiently suppressed.
[0017] The battery according to the fifth aspect of the present disclosure comprises: A positive electrode and A negative electrode; an electrolyte layer disposed between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the sulfide solid electrolyte material according to any one of the first to fourth aspects.
[0018] According to the fifth aspect, it is possible to provide a battery that has excellent output characteristics and generates a small amount of hydrogen sulfide.
[0019] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0020] (Embodiment 1) As shown in FIG. 1, the sulfide solid electrolyte material 10 of this embodiment includes an oxide layer 11 and a sulfide layer 12. The sulfide layer 12 is a layer containing a sulfide material. The oxide layer 11 is a layer containing an oxide of the sulfide material contained in the sulfide layer 12. The oxide layer 11 is located on the surface of the sulfide layer 12. In this embodiment, the sulfide solid electrolyte material 10 has a core-shell structure. The sulfide layer 12 is the core, and the oxide layer 11 is the shell. Hereinafter, the "sulfide solid electrolyte material 10" may be abbreviated as "electrolyte material 10".
[0021] The sulfide material contains Li, P, S and a halogen element X as constituent elements. 31 In the spectrum obtained by P-NMR measurement, the peak component near 88 ppm is defined as a first peak component, the peak intensity of the first peak component is defined as Za, the peak component near 84 ppm is defined as a second peak component, and the peak intensity of the second peak component is defined as Zb. The ratio (Za / Zb) of the peak intensity Za of the first peak component to the peak intensity Zb of the second peak component is 0.42 or less. With this configuration, an electrolyte material 10 that generates a small amount of hydrogen sulfide can be provided.
[0022] In this disclosure, the term "peak component" is not limited to a peak that is evident in a spectrum, but also includes a potential peak component identified by performing multi-Gaussian fitting on a spectrum. In this disclosure, the term "peak component defined within the range of X" means that the apex of the peak component is located within the range of X. The peak width of the peak may be narrower or wider than the range of X.
[0023] A sulfide solid electrolyte material containing Li, P, and S as constituent elements has high ionic conductivity. When X (X: halogen element) is further contained as a constituent element, the ionic conductivity of the sulfide solid electrolyte material can be further increased.
[0024] The sulfide solid electrolyte material containing Li, P, S, and X as constituent elements can have various structures. The ionic conductivity and the amount of hydrogen sulfide generated by the sulfide solid electrolyte material vary depending on the structure.
[0025] For example, a sulfide solid electrolyte material contains Li, P, S, and X as constituent elements, 31 When the sulfide solid electrolyte material has a structure derived from a peak at around 84 ppm in the spectrum obtained by P-NMR measurement, the ionic conductivity of the sulfide solid electrolyte material is high and the amount of hydrogen sulfide generated is small.
[0026] For example, a sulfide solid electrolyte material contains Li, P, S, and X as constituent elements, 31 When the sulfide solid electrolyte material has a structure derived from a peak at around 88 ppm in the spectrum obtained by P-NMR measurement, the ionic conductivity of the sulfide solid electrolyte material is low and the amount of hydrogen sulfide generated is large.
[0027] When a sulfide solid electrolyte material has a sulfide layer and an oxide layer, the oxide layer prevents direct contact between the sulfide layer and moisture. Therefore, the amount of hydrogen sulfide generated can be reduced while maintaining high ionic conductivity. However, when the content ratio of the structure derived from the peak around 88 ppm is high, it is difficult to sufficiently suppress the generation of hydrogen sulfide from the sulfide solid electrolyte material by the oxide layer alone.
[0028] Sulfide solid electrolyte materials 31In a spectrum obtained by P-NMR measurement, a peak component near 88 ppm is defined as a first peak component, a peak intensity of the first peak component is defined as Za, a peak component near 84 ppm is defined as a second peak component, and a peak intensity of the second peak component is defined as Zb. When the ratio (Za / Zb) of the peak intensity Za of the first peak component to the peak intensity Zb of the second peak component is 0.42 or less, the generation of hydrogen sulfide can be sufficiently suppressed.
[0029] 31 In P-NMR measurements, ammonium phosphate can be used as a reference material that shows a chemical shift of 0 ppm. In NMR measurements, the magnetic field conditions are strictly different for each measurement, so a measurement error occurs in the chemical shift output. The measurement error is, for example, ±0.4 ppm. In this disclosure, the phrases "around 88 ppm" and "around 84 ppm" mean "88±0.4 ppm" and "84±0.4 ppm", respectively.
[0030] The halogen element X contained in the electrolyte material 10 of the present embodiment may be I (iodine). In this case, the ion conductivity can be further increased and the amount of hydrogen sulfide generated can be more sufficiently suppressed.
[0031] The sulfide material of the sulfide layer 12 is Li 2 SP 2 S 5 -LiX can be used. 2 SP 2 S 5 Li-LiX has high electrochemical stability and high ionic conductivity. 2 S -P 2 S 5 When Li-LiX is contained in the sulfide layer 12 of the electrolyte material 10, the discharge characteristics of the battery are further improved. 2 SP 2 S 5 The sulfide layer 12 may be mainly composed of LiX. The term "component" means the component that is present in the greatest amount by mass. 2 SP 2 S5 -Li X is, for example, Li 6 P.S. 5 F, Li 6 P.S. 5 Cl, Li 6 P.S. 5 Br, Li 6 P.S. 5 I, Li 7 P 2 S 8 F, Li 7 P 2 S 8 Cl, Li 7 P 2 S 8 Br, Li 7 P 2 S 8 I, αLi 2 S-βP 2 S 5 -(100-α-β)LiF, αLi 2 S-βP 2 S 5 -(100-α-β)LiCl, αLi 2 S-βP 2 S 5 -(100-α-β)LiBr, αLi 2 S-βP 2 S 5 -(100-α-β)LiI (α and β are numbers greater than 0) or the like can be used. The sulfide material may be a crystalline material or a glass material. When the halogen element X is I (iodine), the sulfide material of the sulfide layer 12 may be Li 2 SP 2 S 5 -LiI can be used In this case, the ionic conductivity can be further increased and the amount of hydrogen sulfide generated can be more sufficiently suppressed.
[0032] The oxide layer 11 may be a layer formed by oxidizing the sulfide material contained in the sulfide layer 12. For example, when the sulfide layer 12 contains Li as the sulfide material, 2 SP 2 S 5 -L When the oxide layer 11 contains iX (X: halogen element), the oxide layer 11 contains Li2 SP 2 S 5 -LiX is acid The phrase "the sulfide material contained in the sulfide layer 12 is oxidized" means that some or all of the sulfur bonds in the sulfide material contained in the sulfide layer 12 are replaced with oxygen bonds. For example, when the sulfide layer 12 contains Li as the sulfide material, 2 S- P 2 S 5 -LiX, the sulfur bond is PS, which has four sulfurs bonded to one phosphorus. 4 3- The structure shown in FIG. 1 is mainly included in sulfide materials. In this case, the oxide of the oxide layer 11 is PS 4 3- The structure includes at least one of the structures obtained by replacing some or all of the sulfur bonds of PS 3 O 3- , P.S. 2 O 2 3- , PSO 3 3- and P.O. 4 3- The Can be obtained.
[0033] To confirm that the electrolyte material 10 has an oxide layer 11, 31 For example, the P-NMR measurement can be used. 2 O 2 3- , PSO 3 3- and P.O. 4 3- The peaks attributable to the structure of appear near 70 ppm, 38 ppm, and 10 ppm, respectively.
[0034] The oxide layer 11 located on the surface of the sulfide layer 12 can be confirmed by a combination of etching by ion sputtering and XPS analysis. If the oxide layer 11 is present, a peak attributed to the O1s orbital is clearly observed. Ions used for sputtering include argon ions and C60 cluster ions. If the oxide layer 11 is located on the surface of the sulfide layer 12, the oxygen content decreases continuously from the surface of the electrolyte material 10 (e.g., the surface of a particle) toward the inside of the electrolyte material 10.
[0035] On the other hand, when the oxide layer is uniformly dispersed, the oxygen content shows a constant value from the surface (e.g., the surface of the particle) of the sulfide solid electrolyte material toward the inside. In this case, since the sulfide layer is exposed on the surface of the sulfide solid electrolyte material, it is not possible to sufficiently prevent the sulfide layer from coming into contact with moisture, and it is difficult to sufficiently suppress the generation of hydrogen sulfide.
[0036] The shape of the electrolyte material 10 is not particularly limited. The shape of the electrolyte material 10 is, for example, needle-like, scale-like, spherical, or elliptical. The electrolyte material 10 may be particles. When the electrolyte material 10 is particulate (for example, spherical), the median diameter (d50) of the electrolyte material 10 may be 0.1 μm or more and 100 μm or less. When the electrolyte material 10 has an appropriate size, the ratio (for example, volume ratio) of the oxide layer 11 in the electrolyte material 10 also falls within an appropriate range. This ensures sufficient ion conductivity. When the electrolyte material 10 has an appropriate size, the electrolyte material 10 and other materials such as active materials and conductive assistants can be well dispersed in the positive electrode or negative electrode. These contribute to improving the discharge characteristics of the battery.
[0037] The median particle size of the electrolyte material 10 may be 0.5 μm or more and 10 μm or less. With such a configuration, the ion conductivity can be further increased, and a better dispersion state can be formed between the electrolyte material 10 and other materials such as the active material.
[0038] The median diameter of the particles of the electrolyte material 10 may be smaller than the median diameter of the active material particles. With this configuration, a better dispersion state of the electrolyte material 10 and other materials such as the active material can be achieved.
[0039] The median particle size means the particle size (d50) corresponding to a cumulative 50% volume in the particle size distribution measured by a laser diffraction particle sizer or the like.
[0040] When the electrolyte material 10 is particulate (e.g., spherical), the thickness of the oxide layer 11 may be, for example, 1 nm or more and 300 nm or less, and may be 5 nm or more and 50 nm or less. When the thickness of the oxide layer 11 is adjusted to be within such a range, the ratio of the oxide layer 11 to the electrolyte material 10 falls within an appropriate range. This ensures sufficient ion conductivity.
[0041] The thickness of the oxide layer 11 can be determined by XPS analysis. The oxygen / sulfur element ratio (the ratio of the number of oxygen atoms to the number of sulfur atoms) at the outermost surface of the electrolyte material 10 is defined as "x". The oxygen / sulfur element ratio of the sulfide layer 12 is defined as "z". Ion sputtering and XPS analysis are performed alternately, and XPS spectra are obtained at predetermined intervals (for example, 10 nm intervals). The oxygen / sulfur element ratio is calculated at each depth position. The depth at which the oxygen / sulfur element ratio approximately matches (xz) / 4 can be regarded as the thickness of the oxide layer 11. The oxygen / sulfur elemental ratio "z" of the sulfide layer 12 can also be determined by XPS analysis. For example, if ion sputtering is performed for a sufficient time, the oxygen / sulfur elemental ratio asymptotically decreases toward an asymptotic value. The asymptotic value can be considered as the ratio "z."
[0042] The oxide layer 11 may completely cover the surface of the sulfide layer 12 or may cover only a portion of the surface of the sulfide layer 12 .
[0043] The electrolyte material 10 can be manufactured by the following method.
[0044] Li, P, S, X (X: halogen elements), Li 2 S, P 2 S 5 , precursors including LiX, etc. The raw materials are reacted by methods such as mechanochemical milling and melt quenching, thereby obtaining a glassy sulfide solid electrolyte material.
[0045] When the obtained glass-like sulfide solid electrolyte material is heat-treated, a glass-ceramic-like sulfide solid electrolyte material is obtained. The heat treatment temperature may be lower than 280°C, or may be about 230°C. By carrying out the heat treatment at a temperature lower than 280°C, the precipitation of a crystal phase having a peak near 88 ppm is suppressed. This suppresses the decrease in ion conductivity and the increase in the amount of hydrogen sulfide generated. When the heat treatment temperature is about 230°C, the precipitation of a crystal phase having a peak near 88 ppm is suppressed, and a crystal phase having a peak near 84 ppm is precipitated. This improves the ion conductivity and reduces the amount of hydrogen sulfide generated. The heat treatment time is, for example, 0.1 to 12 hours, and may be 0.5 to 4 hours.
[0046] Next, the glass ceramic-like sulfide solid electrolyte material is placed in an electric furnace controlled to an arbitrary oxygen partial pressure. By heat treating the glass ceramic-like sulfide solid electrolyte material, the sulfide solid electrolyte material reacts with oxygen, and an oxidation treatment is performed. The heat treatment temperature may be a temperature lower than 230 ° C., or may be about 210 ° C. By performing the heat treatment at a temperature lower than 230 ° C., the precipitation of a crystal phase having a peak near 88 ppm is suppressed. This suppresses a decrease in ion conductivity and an increase in the amount of hydrogen sulfide generated. Usually, a crystal phase having a peak near 88 ppm is generated when the heat treatment is performed at a temperature of 280 ° C. or higher. In the oxidation treatment process, the sulfide solid electrolyte material self-heats when the sulfide solid electrolyte material reacts with oxygen. As a result, the temperature of the sulfide solid electrolyte material may locally reach a temperature of 280 ° C. or higher, and a crystal phase having a peak near 88 ppm may be precipitated. Therefore, in the oxidation treatment, the heat treatment temperature may be a temperature lower than 230 ° C. When the heat treatment temperature is about 210° C., the oxidation reaction proceeds at a sufficient reaction rate while suppressing local temperature rise due to self-heating. The lower limit of the heat treatment temperature is, for example, 100° C. The heat treatment time is, for example, 0.1 to 12 hours, and may be 0.5 to 4 hours.
[0047] To control the oxygen partial pressure, oxygen gas may be used. Alternatively, an oxidizing agent that releases oxygen at a predetermined temperature may be used as the oxygen source. The type of oxidizing agent is not particularly limited, and KMnO 4 etc. The inorganic oxidizing agent may be used. The degree of oxidation (e.g., the thickness of the oxide layer 11) can be adjusted by adjusting conditions such as the amount of the oxidizing agent, the installation location of the oxidizing agent, and the filling level of the oxidizing agent. For example, the ratio of oxygen in the electric furnace to the glass ceramic-like sulfide solid electrolyte material is adjusted to 0.1 cc / mg or less. This can prevent oxidation from proceeding excessively.
[0048] Through the above steps, the electrolyte material 10 is obtained.
[0049] (Embodiment 2) In the following embodiment 2, the description overlapping with embodiment 1 will be omitted as appropriate. In the battery according to embodiment 2, the sulfide solid electrolyte material described in embodiment 1 is used.
[0050] As shown in FIG. 2, the battery 20 according to this embodiment includes a positive electrode 21, a negative electrode 23, and an electrolyte layer 22. The positive electrode 21 includes positive electrode active material particles 24 and a sulfide solid electrolyte material 10. The electrolyte layer 22 is disposed between the positive electrode 21 and the negative electrode 23. The electrolyte layer 22 is in contact with both the positive electrode 21 and the negative electrode 23. The electrolyte layer 22 includes the sulfide solid electrolyte material 10. The negative electrode 23 includes the negative electrode active material particles 25 and the sulfide solid electrolyte material 10. The battery 20 is, for example, an all-solid-state lithium secondary battery. The battery 20 according to this embodiment includes the sulfide solid electrolyte material 10 described in the first embodiment, and therefore exhibits excellent output characteristics. The amount of hydrogen sulfide generated in the battery 20 is also small.
[0051] In this embodiment, each of the positive electrode 21, the negative electrode 23, and the electrolyte layer 22 contains the sulfide solid electrolyte material 10. At least the electrolyte layer 22 may contain the sulfide solid electrolyte material 10 of the present disclosure. Among the positive electrode 21, the negative electrode 23, and the electrolyte layer 22, the electrolyte layer 22 contains the largest amount of electrolyte material, so by using the sulfide solid electrolyte material 10 of the present disclosure for the electrolyte layer 22, the amount of hydrogen sulfide generated in the battery 20 can be most efficiently reduced. However, as long as the sulfide solid electrolyte material 10 is contained in at least one selected from the group consisting of the positive electrode 21, the negative electrode 23, and the electrolyte layer 22, the effect of suppressing the generation of hydrogen sulfide can be obtained. Each of the positive electrode 21, the negative electrode 23, and the electrolyte layer 22 may contain a sulfide solid electrolyte material other than the sulfide solid electrolyte material 10 of the present disclosure.
[0052] The positive electrode 21 includes a material having a property of absorbing and releasing metal ions. An example of the metal ion is a lithium ion. The positive electrode 21 includes, for example, a positive electrode active material (for example, positive electrode active material particles 24). The positive electrode 21 may include a sulfide solid electrolyte material 10.
[0053] The positive electrode active material may be a lithium-containing transition metal oxide, a lithium-free transition metal oxide, a transition metal fluoride, a polyanion material, a fluorinated polyanion material, a transition metal sulfide, a transition metal oxyfluoride, a transition metal oxysulfide, a transition metal oxynitride, etc. In particular, when a lithium-containing transition metal oxide is used as the positive electrode active material, the manufacturing cost of the battery 20 can be reduced and the average discharge voltage of the battery 20 can be increased.
[0054] As a positive electrode active material, Li(NiCoAl)O 2 and LiCoO 2 At least one selected from the following may be contained in the positive electrode 21. These transition metal oxides can impart a high energy density to the battery 20.
[0055] The median diameter of the positive electrode active material particles 24 may be 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 24 have an appropriate size, the positive electrode active material particles 24 and the sulfide solid electrolyte material 10 can form a good dispersion state in the positive electrode 21. As a result, excellent discharge characteristics are imparted to the battery 20. In addition, since lithium ions can be quickly diffused inside the positive electrode active material particles 24, it is advantageous for operating the battery 20 at high output. The median diameter of the positive electrode active material particles 24 may be larger than the median diameter of the particles of the sulfide solid electrolyte material 10. This allows the positive electrode active material particles 24 and the sulfide solid electrolyte material 10 to form a good dispersion state.
[0056] In the positive electrode 21, the ratio of the volume v of the positive electrode active material particles 24 to the total volume of the positive electrode active material particles 24 and the volume of the sulfide solid electrolyte material 10 is, for example, 30% or more and 95% or less. The ratio of the volume (100-v) of the sulfide solid electrolyte material 10 is, for example, 5% or more and 70% or less. When the amount of the positive electrode active material particles 24 and the amount of the sulfide solid electrolyte material 10 are appropriately adjusted, the energy density of the battery 20 can be sufficiently ensured and the battery 20 can be operated at high output.
[0057] The thickness of the positive electrode 21 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 21 is appropriately adjusted, the energy density of the battery 20 can be sufficiently ensured, and the battery 20 can be operated at high output.
[0058] The electrolyte layer 22 is a layer including the sulfide solid electrolyte material 10 of the present disclosure. The electrolyte layer 22 may include a second sulfide solid electrolyte material different from the sulfide solid electrolyte material 10 in addition to the sulfide solid electrolyte material 10. In this case, the sulfide solid electrolyte material 10 and the second sulfide solid electrolyte material may be uniformly dispersed in the electrolyte layer 22. The second sulfide solid electrolyte material may have, for example, a composition different from the composition of the sulfide solid electrolyte material 10. The second sulfide solid electrolyte material may have a structure different from the structure of the sulfide solid electrolyte material 10.
[0059] The thickness of the electrolyte layer 22 may be 1 μm or more and 500 μm or less. When the thickness of the electrolyte layer 22 is appropriately adjusted, a short circuit between the positive electrode 21 and the negative electrode 23 can be reliably prevented, and the battery 20 can be operated at high output.
[0060] The battery 20 may include an electrolyte layer 28 shown in FIG. 3 instead of the electrolyte layer 22. The electrolyte layer 28 has a first electrolyte layer 26 and a second electrolyte layer 27. The second electrolyte layer 27 is covered by the first electrolyte layer 26. In detail, the second electrolyte layer 27 is wrapped by the first electrolyte layer 26. The two main surfaces of the electrolyte layer 28 are formed by the first electrolyte layer 26. However, a part of the second electrolyte layer 27 may appear on the surface of the electrolyte layer 28. The "main surface" means the surface having the largest area.
[0061] The first electrolyte layer 26 is a layer including the sulfide solid electrolyte material 10 of the present disclosure. The second electrolyte layer 27 may include the sulfide solid electrolyte material 10, may include the second sulfide solid electrolyte material, or may include both of them. The first electrolyte layer 26 may include more sulfide solid electrolyte material 10 than the second electrolyte layer 27 on a mass basis.
[0062] According to the electrolyte layer 28 shown in FIG. 3, the first electrolyte layer 26 is located around the second electrolyte layer 27, and the second electrolyte layer 27 is protected by the first electrolyte layer 26. The sulfide solid electrolyte material 10 contained in the first electrolyte layer 26 suppresses the intrusion of moisture into the second electrolyte layer 27. This suppresses the generation of hydrogen sulfide caused by the intrusion of moisture into the second electrolyte layer 27. For the second electrolyte layer 27, an electrolyte material that is likely to generate hydrogen sulfide but has a higher ionic conductivity can be used. This allows the ionic conductivity of the battery 20 to be further increased.
[0063] The negative electrode 23 includes a material having a property of absorbing and releasing metal ions. An example of the metal ion is a lithium ion. The negative electrode 23 includes, for example, a negative electrode active material (for example, a negative electrode active material particles 25). The negative electrode 23 may include a sulfide solid electrolyte material 10.
[0064] As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material may be a single metal or an alloy. Examples of the metal material include lithium metal and lithium alloys. Examples of the carbon material include natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, and amorphous carbon. From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds, and tin compounds are preferred. At least one selected from the group consisting of substances can be suitably used as the negative electrode active material.
[0065] The median diameter of the negative electrode active material particles 25 may be 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 25 have an appropriate size, the negative electrode active material particles 25 and the sulfide solid electrolyte material 10 can form a good dispersion state. As a result, excellent discharge characteristics are imparted to the battery 20. In addition, since lithium ions can be quickly diffused inside the negative electrode active material particles 25, it is advantageous for operating the battery 20 at high output. The median diameter of the negative electrode active material particles 25 may be larger than the median diameter of the particles of the sulfide solid electrolyte material 10. This allows the negative electrode active material particles 25 and the sulfide solid electrolyte material 10 to form a good dispersion state.
[0066] In the negative electrode 23, the ratio of the volume V of the negative electrode active material particles 25 to the total volume of the negative electrode active material particles 25 and the volume of the sulfide solid electrolyte material 10 is, for example, 30% or more and 95% or less. The ratio of the volume (100-V) of the sulfide solid electrolyte material 10 to the total volume of the negative electrode active material particles 25 and the volume of the sulfide solid electrolyte material 10 is, for example, 5% or more and 70% or less. When the amount of the negative electrode active material particles 25 and the amount of the sulfide solid electrolyte material 10 are appropriately adjusted, the energy density of the battery 20 can be sufficiently ensured and the battery 20 can be operated at high output.
[0067] The thickness of the negative electrode 23 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 23 is appropriately adjusted, the energy density of the battery 20 can be sufficiently ensured, and the battery 20 can be operated at high output.
[0068] At least one selected from the positive electrode 21, the negative electrode 23, the electrolyte layer 22, the first electrolyte layer 26, and the second electrolyte layer 27 may contain a second sulfide solid electrolyte material different from the sulfide solid electrolyte material 10 for the purpose of increasing ion conductivity. As the second sulfide solid electrolyte material, Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 S.B. 2 S 3 , Li2 S-GeS 2 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 10 GeP 2 S 12 These sulfide materials include LiX (X: F, Cl, Br, I), Li 2 O, M.O. q , Li p MO q (M: P, Si, Ge, B, Al, Ga, In, Fe or Zn) (p, q: natural numbers) or the like may be added.
[0069] At least one selected from the positive electrode 21, the negative electrode 23, the electrolyte layer 22, the first electrolyte layer 26, and the second electrolyte layer 27 may contain an oxide solid electrolyte for the purpose of increasing ion conductivity. 2 (PO 4 ) 3 and its elemental substitution products NASICON-type solid electrolyte, (LaLi)TiO 3 Perovskite-type solid electrolyte Quality, Li 14 ZnGe 4 O 16 , Li 4 SiO 4 , LiGeO 4 and their elemental substitution products, LISICON-type solid electrolytes, Li 7 La 3 Zr 2 O 12 and its element substitution products Garnet-type solid electrolyte, Li 3 N and its H-substituted derivatives, Li 3 PO 4 and its N-substituted derivatives etc. can be used.
[0070] At least one selected from the positive electrode 21, the negative electrode 23, the electrolyte layer 22, the first electrolyte layer 26, and the second electrolyte layer 27 may contain a halide solid electrolyte for the purpose of increasing ion conductivity. 3 InBr 6 , Li 3 InCl 6 , Li 2 FeCl 4 , Li 2 CrCl 4 , Li 3 OCl, etc. may be used.
[0071] At least one selected from the positive electrode 21, the negative electrode 23, the electrolyte layer 22, the first electrolyte layer 26, and the second electrolyte layer 27 may contain a complex hydride solid electrolyte for the purpose of increasing ion conductivity. Examples of the complex hydride solid electrolyte include LiBH 4 - LiI, LiBH 4 -P 2 S 5 etc. may be used.
[0072] At least one selected from the positive electrode 21, the negative electrode 23, the electrolyte layer 22, the first electrolyte layer 26, and the second electrolyte layer 27 may contain an organic polymer solid electrolyte for the purpose of increasing ion conductivity. As the organic polymer solid electrolyte, a compound of a polymer compound and a lithium salt may be used. The polymer compound may have an ethylene oxide structure. By having an ethylene oxide structure, the polymer compound can contain a large amount of lithium salt, so that the ion conductivity can be further increased. As the lithium salt, LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3)(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 Used by As the lithium salt, one type of lithium salt selected from these may be used alone, or a mixture of two or more types of lithium salts selected from these may be used.
[0073] At least one selected from the positive electrode 21, the negative electrode 23, the electrolyte layer 22, the first electrolyte layer 26, and the second electrolyte layer 27 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.
[0074] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, a cyclic carbonate ester solvent, a chain carbonate ester solvent, a cyclic ether solvent, a chain ether solvent, a cyclic ester solvent, a chain ester solvent, a fluorine solvent, etc. can be used. Examples of the cyclic carbonate ester solvent include ethylene carbonate, propylene carbonate, butylene carbonate, etc. Examples of the chain carbonate ester solvent include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, etc. Examples of the cyclic ether solvent include tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, etc. Examples of the chain ether solvent include 1,2-dimethoxyethane, 1,2-diethoxyethane, etc. Examples of the cyclic ester solvent include γ-butyrolactone, etc. Examples of the chain ester solvent include methyl acetate, etc. Examples of fluorine-containing solvents include fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, fluorodimethylene carbonate, etc. As the non-aqueous solvent, one type of non-aqueous solvent selected from these may be used alone, or a mixture of two or more types of non-aqueous solvents selected from these may be used.
[0075] The non-aqueous electrolyte may contain at least one fluorine solvent selected from the group consisting of fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, and fluorodimethylene carbonate. The lithium salt may be LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 As the lithium salt, one selected from these can be used. The lithium salt may be used alone, or a mixture of two or more kinds of lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 to 2 mol / L.
[0076] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0077] The cations constituting the ionic liquid may be aliphatic chain quaternary salts such as tetraalkylammonium and tetraalkylphosphonium, aliphatic cyclic ammoniums such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, and piperidiniums, and nitrogen-containing heterocyclic aromatic cations such as pyridiniums and imidazoliums. The anions constituting the ionic liquid may be PF 6- , B.F. 4 - , SbF 6 - , AsF 6 - , S.O. 3 CF 3 - , N(SO 2 CF 3 ) 2 - , N(SO 2 C 2 F 5 ) 2 - , N(SO 2 CF 3 )(SO 2 C 4 F 9 ) - , C(SO 2 CF 3 ) 3 - The ionic liquid may contain a lithium salt.
[0078] At least one selected from the positive electrode 21, the negative electrode 23, the electrolyte layer 22, the first electrolyte layer 26, and the second electrolyte layer 27 may contain a binder for the purpose of improving adhesion between particles. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, and carboxymethyl cellulose. Copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene may also be used as the binder. A mixture of two or more materials selected from the above may also be used as the binder.
[0079] At least one selected from the positive electrode 21 and the negative electrode 23 may contain a conductive assistant for the purpose of increasing electronic conductivity.
[0080] Examples of the conductive assistant that can be used include graphite such as natural graphite and artificial graphite, carbon black such as acetylene black and ketjen black, conductive fibers such as carbon fibers and metal fibers, metal powders such as carbon fluoride and aluminum powder, conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers, conductive metal oxides such as titanium oxide, and conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene.
[0081] The shape of the conductive assistant is not particularly limited. The shape of the conductive assistant is, for example, needle-like, scale-like, spherical, or elliptical. The conductive assistant may be in the form of particles.
[0082] The positive electrode active material particles 24 and the negative electrode active material particles 25 may be coated with a coating material in order to reduce interface resistance. Only a part of the surface of the positive electrode active material particles 24 may be coated with the coating material, or the entire surface of the positive electrode active material particles 24 may be coated with the coating material. Similarly, only a part of the surface of the negative electrode active material particles 25 may be coated with the coating material, or the entire surface of the negative electrode active material particles 25 may be coated with the coating material.
[0083] As the coating material, a solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, or a complex hydride solid electrolyte can be used. The coating material may be an oxide solid electrolyte. The oxide solid electrolyte has excellent high potential stability. By using the oxide solid electrolyte as the coating material, the charge / discharge efficiency of the battery 20 is improved.
[0084] The oxide solid electrolyte that can be used as the coating material is LiNbO 3 Li-Nb -O compound, LiBO 2 , Li 3 BO 3 Li-BO compounds such as LiAlO 2 Li-Al-O compounds such as Li 4 SiO 4 Li-Si-O compounds such as Li 2 SO 4 , Li 4 Ti 5 O 12 Li-Ti-O compounds such as Li 2 ZrO 3 Li-Zr-O compounds such as Li 2 M oO 3 Li-Mo-O compounds such as LiV 2 O 5 Li-VO compounds such as Li 2 WO 4 Examples of Li-WO compounds include: EXAMPLES
[0085] <Comparative Example 1> In an argon glove box with an Ar atmosphere at a dew point of -60°C or less, 2 S:P 2 S 5 :LiI=60:20:20, so that Li 2 S powder, P 2 S 5 The powder and LiI powder were weighed. These were put into a mortar and crushed and mixed. The mixture was milled for 10 hours at a rotation speed of 510 rpm using a planetary ball mill to obtain a glassy solid electrolyte. The glassy solid electrolyte was heat-treated under an inert atmosphere at 230°C for 2 hours. As a result, a glass-ceramic sulfide solid electrolyte material of Comparative Example 1 was obtained.
[0086] <Comparative Example 2> A glass-ceramic sulfide solid electrolyte material of Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the heat treatment temperature was changed to 280°C.
[0087] <Comparative Example 3> In an argon glove box with an Ar atmosphere at a dew point of -60°C or less, 2 S:P 2 S 5 =75:25, so Li 2 S powder and P 2 S 5 The mixture was milled for 10 hours at a rotation speed of 510 rpm using a planetary ball mill to obtain a glassy solid electrolyte. The glassy solid electrolyte was heat-treated in an inert atmosphere at 270°C for 2 hours. As a result, the glass-ceramic sulfide solid electrolyte material of Comparative Example 3, Li 2 SP 2 S 5 A powder was obtained.
[0088] <Comparative Example 4> In an argon glove box with an Ar atmosphere having a dew point of -60°C or less, the glass-ceramic sulfide solid electrolyte material (Li 2 SP 2 S 5 - LiI, Li 2 S:P 2 S 5 500 mg of sulfide solid electrolyte material (LiI=60:20:20) was weighed out and sealed in a sealed container. After evacuating the inside of the sealed container, 17.5 cc of oxygen gas was introduced into the sealed container. The sealed container was then placed in an electric furnace, and the sulfide solid electrolyte material was heat-treated at 230°C for 450 seconds. This resulted in the sulfide solid electrolyte material of Comparative Example 4. The sulfide solid electrolyte material of Comparative Example 4 has an oxide layer.
[0089] <Comparative Example 5> In an argon glove box with an Ar atmosphere having a dew point of -60°C or less, the glass-ceramic sulfide solid electrolyte material (Li 2 SP 2 S 5 , Li 2 S:P 2 S 5 500 mg of the mixture (mixture of 100% alcohol and 100% water) was weighed out and placed in a sealed container. The inside of the sealed container was evacuated. After that, 28.0 cc of oxygen gas was introduced into the sealed container. Then, the sealed container was placed in an electric furnace, and the sulfide solid electrolyte material was heat-treated under conditions of 300°C and 2400 seconds. As a result, the sulfide solid electrolyte material of Comparative Example 5 was obtained. The sulfide solid electrolyte material of Comparative Example 5 has an oxide layer.
[0090] <Example 1> In an argon glove box with an Ar atmosphere having a dew point of -60°C or less, the glass-ceramic sulfide solid electrolyte material (Li 2 SP 2 S 5 - LiI, Li 2 S:P 2 S 5500 mg of sulfide solid electrolyte material (LiI = 60:20:20) was weighed out and sealed in a sealed container. After evacuating the inside of the sealed container, 17.5 cc of oxygen gas was introduced into the sealed container. The sealed container was then placed in an electric furnace, and the sulfide solid electrolyte material was heat-treated at 210°C for 5000 seconds. In this way, the sulfide solid electrolyte material of Example 1 was obtained. The sulfide solid electrolyte material of Example 1 has an oxide layer.
[0091] [ 31 P-NMR measurement] Using the sulfide solid electrolyte materials of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4, 31 P-NMR measurements were carried out. Ammonium phosphate was used as the standard substance showing a chemical shift of 0 ppm. Sample rotation speed: 20kHz Measurement count: 32 Relaxation time: 30 seconds
[0092] [Measurement of ionic conductivity] The ionic conductivity of the sulfide solid electrolyte materials of Example 1 and Comparative Examples 1 to 5 was measured by the following method.
[0093] 80 mg of sulfide solid electrolyte material was placed in an insulating outer cylinder, and the sulfide solid electrolyte material was pressure-molded at a pressure of 360 MPa to obtain an electrolyte layer. The thickness of the electrolyte layer was measured with a vernier caliper. Next, metal In foil (thickness 200 μm) was placed on each of the upper and lower surfaces of the electrolyte layer. The metal In foil and the electrolyte layer were pressure-molded at a pressure of 80 MPa to produce a laminate consisting of the metal In foil, the electrolyte layer, and the metal In foil. Next, stainless steel current collectors were placed on each of the upper and lower surfaces of the laminate. A current collector lead was attached to each current collector. Finally, the insulating outer cylinder was sealed with an insulating ferrule, and the inside of the insulating outer cylinder was isolated from the outside air. In this way, an electrochemical cell for measuring ionic conductivity was produced.
[0094] The electrochemical cell was placed in a thermostatic chamber at 25° C. Resistance measurements were performed by an AC impedance method under conditions of a voltage amplitude of ±10 mV and a measurement frequency of 0.01 Hz to 1 MHz. Ionic conductivity was calculated using the measured resistance value, the area of the electrodes, and the thickness of the electrolyte layer.
[0095] [Measurement of hydrogen sulfide generation] The amounts of hydrogen sulfide generated from the sulfide solid electrolyte materials of Example 1 and Comparative Examples 1 to 5 were measured by the following method.
[0096] In an argon glove box with an Ar atmosphere at a dew point of -60°C or less, 80 mg of sulfide solid electrolyte material was weighed out. The weighed sulfide solid electrolyte material was placed in a powder molding die with an inner diameter of 9.5 mm and pressure-molded at a pressure of 360 MPa. After molding, pellets of the sulfide solid electrolyte material were removed from the powder molding die and placed in a sealable glass container. The glass container was placed in a thermostatic chamber with a humidified atmosphere at a temperature of 25°C and a relative humidity of 50%, and the inside of the glass container was replaced with a humidified atmosphere. The glass container was then sealed, and the pellets were exposed to the humidified atmosphere for 60 minutes. The amount of hydrogen sulfide inside the glass container 60 minutes after the glass container was sealed was measured using a portable gas monitor (Riken Keiki Co., Ltd., GX-2012). The amount of hydrogen sulfide was divided by the weight of the pellets to determine the amount of hydrogen sulfide generated per unit weight (cm 3 / g) was calculated.
[0097] [XPS Measurement] XPS measurement of the sulfide solid electrolyte material of Example 1 was carried out under the following conditions. Sputtering of the sulfide solid electrolyte material with C60 cluster ions and XPS measurement were repeatedly carried out. That is, XPS depth analysis was carried out under the following conditions. Peak area intensities in the four obtained spectra were calculated. The oxygen content (atom%) of the sulfide solid electrolyte material was calculated from the peak area intensity of oxygen (O) relative to the sum of the peak area intensities of oxygen (O), lithium (Li), phosphorus (P) and sulfur (S).
[0098] Measurement device: PHI VersaProbe X-ray source: Monochromated AlKα radiation (1486.6 eV) Measured spectrum: O1s, Li1s, P2p, S2p Sputtering conditions: C60+, 10.0 kV Sputtering rate: Approximately 2 nm / min (SiO 2 Conversion)
[0099] FIG. 4 shows the sulfide solid electrolyte materials of Example 1, Comparative Example 1, and Comparative Example 4. 31 1 is a graph showing the results of P-NMR measurement. Comparative Example 1 had no peak in the range of -20 to 50 ppm. Comparative Example 4 and Example 1 had peaks near 38 ppm and near 10 ppm, respectively. The peaks near 38 ppm and near 10 ppm were due to PSO 3 3- Structure and PO 4 3- That is, in Comparative Example 4 and Example 1, at least the PSO 3 3- Structure and PO 4 3- Comparative Example 1 had no oxide layer.
[0100] FIG. 5 is a graph showing the results of XPS measurement of the sulfide solid electrolyte material of Example 1. The graph specifically shows the relationship between the sputtering time and the oxygen content. The oxygen content was high in the region where the sputtering time was short, i.e., in the region close to the surface of the sulfide solid electrolyte material. The oxygen content was low in the region where the sputtering time was long, i.e., in the inner region of the sulfide solid electrolyte material. The oxygen content was continuously reduced from the surface to the inside of the sulfide solid electrolyte material. From the results shown in FIG. 5, it was confirmed that an oxide layer was located in the surface layer portion of the sulfide solid electrolyte material of Example 1.
[0101] FIG. 6 shows the results of the sulfide solid electrolyte materials of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 4. 311 is a graph showing the results of P-NMR measurement. The spectra of Comparative Example 2 and Comparative Example 4 showed peaks near 88 ppm and near 84 ppm. The spectra of Comparative Example 1 and Example 1 showed a peak near 84 ppm, but almost no peak was confirmed near 88 ppm.
[0102] The ionic conductivity and hydrogen sulfide generation amount of the sulfide solid electrolyte materials of Example 1 and Comparative Examples 1 to 5 are shown in Table 1. 31 The peak intensity ratio (Za / Zb) was calculated from the P-NMR measurement results. The results are shown in Table 1. Peak intensity Za is the peak intensity of the first peak component near 88 ppm. Peak intensity Zb is the peak intensity of the second peak component near 84 ppm.
[0103] The peak intensities were calculated by the following method. That is, the obtained spectrum was fitted using a Gaussian distribution. Even when no peak was substantially observed near 88 ppm, as in the spectra of Example 1 and Comparative Example 1, the spectrum was fitted on the assumption that a first peak component was present near 88 ppm. Instead of the intensities of the peaks contained in the actually obtained spectrum, the intensities of each peak in the fitting curve can be adopted as the peak intensities Za and Zb.
[0104] Specifically, the peak positions of the first peak component in Comparative Examples 1, 2, and 4 and Example 1 were set to 88.0 ppm, 87.9 ppm, 88.1 ppm, and 88.0 ppm, respectively. The peak positions of the second peak component in Comparative Examples 1, 2, and 4 and Example 1 were set to 83.7 ppm, 84.2 ppm, 84.0 ppm, and 84.1 ppm, respectively.
[0105] In the fitting of Example 1 and Comparative Example 1, in addition to the first and second peak components, a peak component near 92 ppm and a peak component near 78 ppm were set to exist.
[0106] [Table 1]
[0107] Comparative Example 3 and Comparative Example 5 did not contain a halogen element as a constituent element, and therefore their ionic conductivity was 1×10 -3 The amount of hydrogen sulfide generated in Comparative Example 3 and Comparative Example 5 was 1×10 -2 cm 3 / g. The amount of hydrogen sulfide generated was less than that of Comparative Example 3, which does not have an oxide layer. When halogen elements are not included as constituent elements, the crystal structure of the sulfide material is less likely to change even if the solid electrolyte material is heat-treated at a high temperature of 300°C in the process of forming the oxide layer, and the precipitation of a crystal phase having a peak near 88 ppm is suppressed. Therefore, a solid electrolyte material with high ionic conductivity and low hydrogen sulfide generation is obtained. In addition, the oxide layer suppresses contact between the sulfide layer and moisture, so that the generation of hydrogen sulfide is further suppressed.
[0108] Comparative Example 1 mainly contained a structure derived from the second peak component at around 84 ppm. The ionic conductivity of Comparative Example 1 was high. The amount of hydrogen sulfide generated in Comparative Example 1 was relatively small. However, the amount of hydrogen sulfide generated in Comparative Example 1 was 1×10 -2 cm 3 / g or more, and what is considered to be sufficiently small is I can't say.
[0109] Comparative Example 2 contained both the structure derived from the first peak component at about 88 ppm and the structure derived from the second peak component at about 84 ppm. The ionic conductivity of Comparative Example 2 was low. The amount of hydrogen sulfide generated in Comparative Example 2 was large.
[0110] Comparative Example 4 had an oxide layer. Comparative Example 4 was obtained through oxidation treatment at 230°C. Therefore, Comparative Example 4 had a structure derived from the first peak component at around 88 ppm. As a result, in Comparative Example 4, the ion conductivity decreased and the amount of hydrogen sulfide generated increased.
[0111] Example 1 was obtained through oxidation treatment at 210°C. Therefore, Example 1 had almost no structure derived from the first peak component near 88 ppm. In Example 1, the ratio (Za / Zb) of the peak intensity Za of the first peak component near 88 ppm to the peak intensity Zb of the second peak component near 84 ppm was 0.42. Therefore, Example 1 had a 1×10 -3 High ionic conductivity of over 1×10 S / cm -2 cm 3 / g or less low sulfur water The ionic conductivity is, for example, 1×10 -3 S / cm or more. The higher the ionic conductivity, the more desirable it is, so there is no upper limit to its value.
[0112] The lower limit of the peak intensity ratio (Za / Zb) is not particularly limited, and is theoretically zero.
[0113] As described above, the formation of an oxide layer suppresses the generation of hydrogen sulfide. When an oxide layer is formed on the surface of a sulfide solid electrolyte material containing LiX, the crystal structure may change due to self-heating caused by oxidation. According to the technology disclosed herein, the change in the crystal structure is suppressed by sufficiently lowering the heat treatment temperature when forming the oxide layer. As a result, a sulfide solid electrolyte material that generates a small amount of hydrogen sulfide is obtained. [Industrial Applicability]
[0114] The disclosed technology is useful for, for example, all-solid-state lithium secondary batteries. [Explanation of symbols]
[0115] 10 Sulfide solid electrolyte materials 11 Oxide layer 12 Sulfide layer 20 batteries 21 Positive electrode 22 Electrolyte layer 23 Negative electrode 24 Positive electrode active material particles 25 Negative electrode active material particles 26 First electrolyte layer 27 Second electrolyte layer 28 Electrolyte layer
Claims
1. a sulfide layer including a sulfide containing lithium, phosphorus, a halogen, and sulfur; An oxide layer is disposed on the sulfide layer and includes an oxide containing lithium, phosphorus, a halogen, and oxygen. The sulfide solid electrolyte material 31 In the P-NMR spectrum, the intensity of a first peak component defined in a chemical shift range of 87.6 ppm to 88.4 ppm is 0.42 times or less than the intensity of a second peak component defined in a chemical shift range of 83.6 ppm to 84.4 ppm. Sulfide solid electrolyte material.
2. The structure of the oxide has a structure in which the sulfur in the sulfide is at least partially substituted with the oxygen. The sulfide solid electrolyte material according to claim 1.
3. The oxide consists of all elements constituting the sulfide and the oxygen, The sulfide solid electrolyte material according to claim 1 or 2.
4. The halogen is iodine. The sulfide solid electrolyte material according to any one of claims 1 to 3.
5. The sulfide is Li 2 S-P 2 S 5 -LiX, where X is the halogen; The sulfide solid electrolyte material according to any one of claims 1 to 3.
6. wherein X is I; The sulfide solid electrolyte material according to claim 5 .
7. The sulfide solid electrolyte material excludes sulfide solid electrolyte materials containing lithium, phosphorus, sulfur, chlorine, and bromine. The sulfide solid electrolyte material according to claim 1.
8. The above 31 The P-NMR spectrum was 3 3- Structure and PO 4 3- having peaks corresponding to the structure, The sulfide solid electrolyte material according to any one of claims 1 to 7.
9. A positive electrode and A negative electrode; an electrolyte layer disposed between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the sulfide solid electrolyte material according to any one of claims 1 to 6, battery.
Citation Information
Patent Citations
Sulfide solid electrolyte particle
JP2012094445A
Electrode material and lithium ion battery manufactured using the same
JP2013110051A
Solid electrolyte
JP2013118092A
Solid electrolyte
JP2013201110A
Storage method and storage device of solid electrolyte, and manufacturing method of all solid state battery
JP2013201111A